Negative electrode material, preparation method thereof, negative electrode sheet, and battery
Patent Information
- Application Number
- CN202611184471.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-05
- Publication Date
- 2026-10-30
AI Technical Summary
然而,硅材料在充放电过程中因巨大的体积膨胀导致电极材料结构粉化,从而造成负极容量快速衰减
(1)本申请利用表面化学改性实现异质材料的均匀复合,硅纳米片表面因天然氧化层(SiOx)的存在,在水溶液中通常呈现弱负电性,与同样带负电的MXene纳米片之间存在静电斥力,难以直接形成均匀稳定的复合结构。而本申请通过阳离子表面活性剂对硅纳米片进行改性,阳离子表面活性剂的疏水端通过范德华力吸附于硅纳米片表面,而亲水的阳离子头基则向外伸展,使硅纳米片表面电荷由负转正。当带正电的改性硅纳米片的分散液与带负电的MXene纳米片的分散液混合时,两者之间产生强烈的静电引力,驱动硅纳米片自发地、均匀地锚定在MXene纳米片表面或嵌入层间间隙,形成紧密接触的异质结构。这种自组装过程无需外加能量,反应条件温和,且复合均匀。
Smart Images

Figure CN123017923A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of battery technology, and in particular to a negative electrode material and its preparation method, a negative electrode sheet, and a battery. Background Technology
[0002] Silicon is widely used as an anode material in lithium-ion batteries due to its extremely high theoretical specific capacity. However, the massive volume expansion of silicon during charging and discharging leads to pulverization of the electrode material structure, resulting in rapid capacity decay of the anode. Furthermore, the poor intrinsic conductivity and lithium-ion diffusion coefficient of silicon further limit the rate performance of the anode. Summary of the Invention
[0003] This application provides a negative electrode material, its preparation method, a negative electrode sheet, and a battery. The technical solution is as follows: On one hand, a negative electrode material is provided, the negative electrode material comprising: modified silicon nanosheets and MXene nanosheets, wherein the modified silicon nanosheets are attached to the surface of the MXene nanosheets.
[0004] In one possible implementation, the planar lateral dimension of the modified silicon nanosheet is 0.1 μm to 10 μm.
[0005] In another possible implementation, the thickness of the modified silicon nanosheets is 100 nm to 200 nm.
[0006] In another possible implementation, the modified silicon nanosheets are obtained by modifying silicon nanosheets with a cationic surfactant.
[0007] In another possible implementation, the cationic surfactant is selected from at least one of polydiallyldimethylammonium chloride, polymethacryloyloxyethyltrimethylammonium chloride, and polyethyleneimine.
[0008] In another possible implementation, the silicon nanosheets are selected from photovoltaic silicon waste.
[0009] In another possible implementation, the MXene nanosheets are selected from Ti3C2T. x Ti2CT x V2CT x At least one of Nb2CTx; T x The functional groups of the MXene nanosheets are represented.
[0010] On the other hand, a method for preparing a negative electrode material is provided, wherein the negative electrode material is as described in any of the above claims, and the preparation method includes: A dispersion of modified silicon nanosheets was obtained by modifying silicon nanosheets with a cationic surfactant. Preparation of dispersions of MXene nanosheets; The dispersion of the modified silicon nanosheets was mixed with the dispersion of the MXene nanosheets, and then freeze-dried to obtain the negative electrode material.
[0011] On the other hand, a negative electrode sheet is provided, the negative electrode sheet comprising the negative electrode material described in any of the above claims or the negative electrode material prepared by the above preparation method.
[0012] On the other hand, a battery is provided, the battery comprising: a housing, an electrolyte contained inside the housing, a negative electrode, a positive electrode, and a separator, wherein the negative electrode is as described above, and the negative electrode and the positive electrode are separated by the separator.
[0013] This application provides an anode material comprising modified silicon nanosheets and MXene nanosheets, with the modified silicon nanosheets adhered to the surface of the MXene nanosheets to form a tightly contacted heterostructure. MXene nanosheets possess metal-like high conductivity, several to tens of times that of traditional carbon materials. In the anode material, the MXene nanosheets overlap to construct a three-dimensional, multi-level conductive network. Since both the modified silicon nanosheets and the MXene nanosheets are two-dimensional sheets, they form a "surface-to-surface" contact structure. On one hand, this "surface-to-surface" contact structure significantly increases the contact area between the two phases, enhancing the electrostatic adsorption between the modified silicon nanosheets and the MXene nanosheets, improving the overall stability of the composite structure, and constructing a continuous and wide electron transport channel, effectively reducing the interfacial resistance between the two phases. On the other hand, in this "surface-to-surface" contact structure, the volume expansion stress generated by the modified silicon nanosheets during lithiation / delithiation can be uniformly transferred to the tightly adhered MXene nanosheets, avoiding particle breakage or interface delamination problems caused by localized stress concentration in "point-to-surface" contact structures. As can be seen, the negative electrode material provided in this application embodiment has high capacity, high conductivity and high structural stability, and can achieve high reversible capacity, long cycle life and excellent rate performance during charging and discharging. Attached Figure Description
[0014] Figure 1 This is a side cross-sectional view of a negative electrode material provided in an embodiment of this application; Figure 2 These are TEM and EDS images of a negative electrode material provided in Embodiment 1 of this application; Figure 3 This is a schematic diagram of a rate capability provided in an embodiment of this application; Figure 4 This is an electrochemical impedance spectroscopy provided in an embodiment of this application. Detailed Implementation
[0015] To make the technical solution and advantages of this application clearer, the embodiments of this application will be described in further detail below.
[0016] On one hand, embodiments of this application provide a negative electrode material, which includes: modified silicon nanosheets and MXene nanosheets, wherein modified silicon nanosheets are bonded to the surface of MXene nanosheets.
[0017] This application provides an anode material comprising modified silicon nanosheets and MXene nanosheets, with the modified silicon nanosheets adhered to the surface of the MXene nanosheets to form a tightly contacted heterostructure. MXene nanosheets possess metal-like high conductivity, several to tens of times that of traditional carbon materials. In the anode material, the MXene nanosheets overlap to construct a three-dimensional, multi-level conductive network. Since both the modified silicon nanosheets and the MXene nanosheets are two-dimensional sheets, they form a "surface-to-surface" contact structure. On one hand, this "surface-to-surface" contact structure significantly increases the contact area between the two phases, enhancing the electrostatic adsorption between the modified silicon nanosheets and the MXene nanosheets, improving the overall stability of the composite structure, and constructing a continuous and wide electron transport channel, effectively reducing the interfacial resistance between the two phases. On the other hand, in this "surface-to-surface" contact structure, the volume expansion stress generated by the modified silicon nanosheets during lithiation / delithiation can be uniformly transferred to the tightly adhered MXene nanosheets, avoiding particle breakage or interface delamination problems caused by localized stress concentration in "point-to-surface" contact structures. As can be seen, the negative electrode material provided in this application embodiment has high capacity, high conductivity and high structural stability, and can achieve high reversible capacity, long cycle life and excellent rate performance during charging and discharging.
[0018] In one possible implementation, the planar lateral dimensions of the modified silicon nanosheets are 0.1 μm to 10 μm.
[0019] In this implementation, the planar lateral dimension of the modified silicon nanosheet refers to the planar length or width of the modified silicon nanosheet.
[0020] For example, the planar transverse dimensions of the modified silicon nanosheets can be 0.1μm, 0.5μm, 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, etc.
[0021] In the embodiments of this application, the planar lateral dimensions of the modified silicon nanosheets are within the aforementioned range, allowing them to match the MXene nanosheets and form a surface-to-surface contact. On one hand, this surface-to-surface contact structure can significantly increase the contact area between the two phases, enhancing the electrostatic adsorption between the modified silicon nanosheets and the MXene nanosheets, improving the overall stability of the composite structure, and constructing a continuous and wide electron transport channel, effectively reducing the interfacial resistance between the two phases. On the other hand, in this surface-to-surface contact structure, the volume expansion stress generated by the modified silicon nanosheets during lithiation / delithiation can be uniformly transferred to the tightly bonded MXene nanosheets, avoiding the particle breakage or interface delamination problems caused by local stress concentration in the point-to-surface contact structure.
[0022] Furthermore, if the planar lateral dimension of the modified silicon nanosheets is <0.1μm, the specific surface area of the modified silicon nanosheets is too large, leading to continuous decomposition of the electrolyte and the formation of a thick and unstable SEI (Solid Electrolyte Interface), which consumes active lithium and causes rapid capacity decay. If the planar lateral dimension of the modified silicon nanosheets is greater than 10μm, the lithium-ion diffusion path becomes too long, and the modified silicon nanosheets experience stress concentration and are prone to breakage. Therefore, controlling the planar lateral dimension of the modified silicon nanosheets within the above-mentioned range can achieve a moderate specific surface area, reduce side reactions, and retain sufficient ion reaction sites, thus balancing high reversible capacity and cycle stability.
[0023] In one possible implementation, the thickness of the modified silicon nanosheets is 100 nm to 200 nm.
[0024] For example, the thickness of the modified silicon nanosheets can be 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 160nm, 170nm, 180nm, 190nm, 200nm, etc.
[0025] In the embodiments of this application, the thickness of the modified silicon nanosheets is within the aforementioned range, which can significantly shorten the diffusion path of lithium ions. Under high-rate charge and discharge, lithium ions can quickly complete lithium intercalation, alleviating concentration polarization and achieving rapid energy storage by matching the highly conductive MXene framework. Furthermore, the thickness of the modified silicon nanosheets within the aforementioned range can also combine mechanical toughness with the ability to uniformly release stress. Expansion stress can be uniformly transferred to the MXene nanosheets, avoiding stress concentration that could lead to silicon wafer shattering and breakage of the conductive network.
[0026] In one possible implementation, the modified silicon nanosheets are obtained by modifying silicon nanosheets with a cationic surfactant.
[0027] In this embodiment, silicon nanosheets exhibit weak negative charge in aqueous solution due to the presence of a natural oxide layer. This leads to electrostatic repulsion between silicon nanosheets and MXene nanosheets, which are also negatively charged, making it difficult to directly form a uniform and stable composite structure. Therefore, a cationic surfactant is introduced to modify the silicon nanosheets, making their surface uniformly positively charged. This generates a strong electrostatic attraction between the modified silicon nanosheets and MXene nanosheets, driving the modified silicon nanosheets to spontaneously and uniformly anchor on the surface of MXene nanosheets or embed in the interlayer gaps, forming a closely contacted heterostructure.
[0028] See Figure 1 , Figure 1 This is a side cross-sectional view of a negative electrode material according to an embodiment of this application. Figure 1 As can be seen, after modification of silicon nanosheets with cationic surfactants, the upper and lower surfaces of the silicon nanosheets are uniformly positively charged, while the surface of the MXene nanosheets is negatively charged. Due to electrostatic attraction, the silicon nanosheets are embedded in the interlayer gaps of the MXene nanosheets, forming a sandwich-like structure. The MXene nanosheets are Ti3C2T. x T x The functional groups representing MXene nanosheets are -O, -OH, -F, etc.
[0029] In one possible implementation, the cationic surfactant is selected from at least one of polydiallyldimethylammonium chloride, polymethacryloyloxyethyltrimethylammonium chloride, and polyethyleneimine.
[0030] In this implementation, the hydrophobic end of the aforementioned cationic surfactant is adsorbed onto the surface of the silicon nanosheet via van der Waals forces, while the hydrophilic cationic head group extends outward, causing the surface potential of the silicon nanosheet to change from negative to positive, thereby generating a strong electrostatic attraction with the MXene nanosheet.
[0031] In one possible implementation, the silicon nanosheets are selected from photovoltaic silicon waste.
[0032] While providing clean energy to society, the photovoltaic industry also generates a large amount of solid waste, especially silicon waste produced during the cutting, grinding, or crushing of silicon wafers, namely photovoltaic silicon waste. Photovoltaic silicon waste has high purity, but its surface often has an amorphous oxide layer. If it is directly landfilled or treated at a low value, it will not only waste high-purity silicon resources, but also pose potential environmental risks.
[0033] This application directly uses silicon waste generated in the photovoltaic industry chain as a silicon source, which not only significantly reduces the raw material cost of lithium-ion battery anode materials, but also provides a green and high-value-added recycling path for the treatment of photovoltaic waste, transforming photovoltaic silicon waste, which was originally treated as solid waste, into high-value-added lithium-ion battery anode materials.
[0034] In one possible implementation, MXene nanosheets are selected from Ti3C2T. x Ti2CT x V2CT x At least one of Nb2CTx.
[0035] MXenes are a class of two-dimensional transition metal carbides, nitrides, or carbonitrides with hydroxyl groups or terminal oxygen functional groups on their surface. They possess pseudocapacitive energy storage properties, metallic-grade conductivity, and high surface chemical activity, showing broad application prospects in electrochemical energy storage. MXenes can be used as active materials or as conductive matrix materials. When used as active materials, MXenes exhibit high theoretical specific capacity (447.8 mAh / g) and fast lithium-ion transport performance. When used as conductive matrix materials, MXenes can be composited with high-capacity but low-conductivity active materials to prepare MXene-based composite electrode materials. This application composites MXenes with modified silicon nanosheets, which not only provides a fast electron transport channel for the modified silicon nanosheets but also buffers their volume changes and MXene aggregation during charge and discharge, thereby achieving high specific capacity and good cycle and rate performance.
[0036] Among them, T x The functional groups representing MXene nanosheets include, for example, —O, —OH, —F, etc. These polar functional groups not only endow MXene with good water dispersibility, facilitating the electrostatic self-assembly process, but also can form hydrogen bonds or chemical bonds with the oxide layer on the surface of silicon nanosheets, enhancing interfacial adhesion. After heat treatment, some of these functional groups are removed, and Si-OM (M represents transition metals such as Ti, V, Nb) chemical bonds may be formed, further strengthening the interfacial adhesion.
[0037] This application utilizes silicon nanosheets anchored to an MXene conductive network to achieve an efficient combination of high-capacity active material and a highly conductive framework. MXene serves as both a conductive channel to improve rate performance and a buffer layer to suppress volume expansion. Meanwhile, the natural oxide layer on the surface of the silicon nanosheets also plays an auxiliary buffering role.
[0038] On the other hand, embodiments of this application provide a method for preparing a negative electrode material, the method comprising: Step 101: Modify silicon nanosheets with a cationic surfactant to obtain a dispersion of modified silicon nanosheets.
[0039] First, silicon nanosheets are pretreated by cleaning, drying and pulverizing to obtain silicon powder. Then, the silicon powder and cationic surfactant are dispersed in water to obtain a dispersion of modified silicon nanosheets.
[0040] Cleaning the silicon nanosheets removes impurities adhering to their surface, preventing interference with subsequent electrostatic self-assembly. Drying the silicon nanosheets removes surface moisture, avoiding dilution of solutions containing cationic surfactants. Pulverizing the silicon nanosheets ensures uniform and standardized length, width, and thickness, matching the two-dimensional scale of MXene and achieving surface-to-surface bonding, unlike the point contact mode of spherical silicon particles.
[0041] As an example, a cationic surfactant is first dissolved in deionized water to obtain a solution. Then, silicon powder is dispersed in the solution, followed by ultrasonic dispersion and stirring to allow the cationic surfactant to be fully adsorbed on the surface of the silicon powder, causing the surface charge of the silicon to change from negative to positive. Then, the silicon powder is separated by centrifugation using a high-speed centrifuge, the supernatant is discarded, and the powder is repeatedly washed with deionized water. The washed modified silicon powder is then redispersed in an appropriate amount of deionized water to obtain a dispersion of modified silicon nanosheets.
[0042] The ultrasound duration can be 1 hour to 2 hours. For example, the ultrasound duration can be 1 hour, 1.2 hours, 1.5 hours, 1.8 hours, 2 hours, etc.
[0043] The stirring time can be 1 hour to 2 hours. For example, the stirring time can be 1 hour, 1.2 hours, 1.5 hours, 1.8 hours, 2 hours, etc.
[0044] In this implementation, the mass ratio of silicon nanosheets to cationic surfactant is 1:(0.3~2).
[0045] For example, the mass ratio of silicon nanosheets (i.e., silicon powder) to cationic surfactant can be 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9, 1:2, etc.
[0046] In the embodiments of this application, if the mass ratio of silicon nanosheets to cationic surfactant is less than 0.3, the charge on the surface of the silicon nanosheets cannot be completely converted from negative to positive. If the mass ratio is greater than 2, excessive free positively charged cationic surfactant will preferentially bind to MXene, resulting in a smaller amount of MXene composited with the silicon nanosheets. Therefore, controlling the mass ratio within the above range allows for a complete conversion of the charge on the surface of the silicon nanosheets from negative to positive, while also enabling the formation of a stable electrostatic attraction with MXene, achieving large-area surface-to-surface bonding.
[0047] Step 102: Prepare a dispersion of MXene nanosheets.
[0048] In one possible implementation, if MXene is purchased pre-etched MXene material, the process can be as follows: disperse the MXene material in water, and obtain a dispersion of MXene nanosheets by ultrasonic dispersion and centrifugation.
[0049] The ultrasound duration can be set and changed as needed, without any specific limitation. For example, the ultrasound duration can be 1 hour to 2 hours. Examples include 1 hour, 1.2 hours, 1.5 hours, 1.8 hours, and 2 hours.
[0050] Centrifugation time can be set and changed as needed, and there is no specific limitation. For example, the centrifugation time can be 0.5h to 1h. For example, the centrifugation time can be 0.5h, 0.6h, 0.7h, 0.8h, 0.9h, 1h, etc.
[0051] After centrifugation, the bottom precipitate was discarded, and the supernatant was collected to obtain a dispersion of MXene nanosheets.
[0052] In another possible implementation, a dispersion of MXene nanosheets is prepared by etching the corresponding MXene phase raw material. Accordingly, this process can be achieved through the following steps: (1) Prepare etching solution.
[0053] LiF was dissolved in a 9 mol / L to 12 mol / L hydrochloric acid solution to obtain the etching solution.
[0054] The mass-to-volume ratio of LiF to hydrochloric acid is (1.6~2) g: (20~30) mL.
[0055] For example, the mass-to-volume ratio of LiF to hydrochloric acid can be 1.6g:20mL, 1.7g:20mL, 1.8g:20mL, 1.9g:20mL, 2g:20mL, 1.6g:25mL, 1.7g:25mL, 1.8g:25mL, 1.9g:25mL, 2g:25mL, 1.6g:30mL, 1.7g:30mL, 1.8g:30mL, 1.9g:30mL, 2g:30mL, etc.
[0056] (2) The MXene material is etched by etching solution to obtain crude MXene product.
[0057] MXene material was slowly added to the etching solution and stirred in a water bath at 30℃~40℃ for 20h~30h to obtain crude MXene product.
[0058] For example, the water bath temperature can be 30℃, 32℃, 35℃, 38℃, 40℃, etc. The stirring time can be 20h, 22h, 25h, 28h, 30h, etc.
[0059] In this embodiment of the application, the MXene material is etched by an etching solution to transform the MXene material from a block shape to a sheet shape.
[0060] (3) The crude MXene product was washed, ultrasonically dispersed, and centrifuged to obtain a dispersion of MXene nanosheets.
[0061] The crude MXene product was repeatedly washed with deionized water and centrifuged until the pH of the supernatant was greater than 6. Then, it was ultrasonically dispersed, followed by centrifugation, and the supernatant was collected to obtain a dispersion of MXene nanosheets.
[0062] The ultrasonic time can be 1 to 2 hours, and the centrifugation time can be 0.5 to 1 hour.
[0063] Step 103: Mix the dispersion of modified silicon nanosheets with the dispersion of MXene nanosheets, and freeze-dry to obtain the anode material.
[0064] The dispersion of modified silicon nanosheets was mixed with the dispersion of MXene nanosheets, stirred at room temperature for 0.5 h to 2 h, filtered, and then freeze-dried to obtain the anode material.
[0065] The mass ratio of MXene nanosheets to silicon nanosheets is 1:(5~20). For example, the mass ratio of MXene nanosheets to silicon nanosheets can be 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, 1:16, 1:17, 1:18, 1:19, or 1:20.
[0066] In the embodiments of this application, the mass ratio of MXene nanosheets to silicon nanosheets is within the above-mentioned range, which can maximize the high capacity contribution of silicon and improve the specific capacity of the material and the energy density of the battery.
[0067] For example, the stirring time at room temperature can be 0.5h, 0.8h, 1h, 1.2h, 1.5h, 1.8h, 2h, etc.
[0068] After stirring, the mixture is filtered to obtain a filter cake. The filter cake is then rapidly pre-frozen with liquid nitrogen and transferred to a freeze dryer. It is freeze-dried at -60℃ to -70℃ for 10 to 12 hours to obtain the negative electrode material.
[0069] The freeze-drying temperature can be -60℃, -62℃, -65℃, -68℃, -70℃, etc. The freeze-drying time can be 10h, 10.5h, 11h, 11.5h, 12h, etc.
[0070] In the embodiments of this application, by controlling the temperature and time of freeze-drying, the negative electrode material is obtained by freeze-drying. The water sublimates directly, the silicon is not easily oxidized to silicon oxide, and there is no capillary contraction force. The loose three-dimensional porous network of modified silicon nanosheets and MXene nanosheets can be completely preserved. The MXene nanosheets are not easy to stack, and the modified silicon nanosheets are uniformly dispersed.
[0071] If conventional low-temperature vacuum drying is used, silicon is easily oxidized to silicon oxide, resulting in a significant decrease in discharge specific capacity. Furthermore, water evaporation involves capillary surface tension, causing MXene nanosheets to aggregate under tensile forces during the drying process. The surface-to-surface bonding structure between the modified silicon nanosheets and MXene nanosheets shrinks and collapses, significantly reducing the porosity of the three-dimensional conductive network and thus affecting the electrochemical performance of the material.
[0072] Unlike traditional silicon particle / MXene composites that rely on mechanical mixing, chemical cross-linking, or high-temperature calcination, this application employs cationic surfactants to modify the surface of silicon nanosheets, resulting in a uniformly positively charged surface. This allows for close and uniform self-assembly of the silicon nanosheets with MXene nanosheets via electrostatic forces. This strategy not only avoids the structural damage caused by chemical bonding but also achieves a uniform and tight bond between silicon nanosheets and MXene at the microscale, significantly improving interfacial stability. This electrostatic self-assembly method is carried out entirely in an aqueous phase, eliminating the need for complex vapor deposition equipment or energy-intensive ball milling processes. The reaction conditions are ambient temperature and pressure, offering a wide process window and simple operation. It avoids high-temperature, high-pressure, or complex chemical bonding processes. Furthermore, the electrostatic self-assembly process is spontaneous, driven by charge, resulting in high raw material utilization and good product uniformity, making it highly suitable for industrial-scale production. In the obtained composite material, MXene nanosheets serve as a conductive framework, providing a continuous electron transport path for silicon nanosheets and reducing electrode polarization. They can also effectively alleviate the huge volume changes of silicon nanosheets during lithiation and delithiation processes, reduce the continuous growth of the solid electrolyte interface film, and thus significantly improve the rate performance and cycle performance of the electrode.
[0073] On the other hand, embodiments of this application provide a negative electrode sheet, which includes the aforementioned negative electrode material.
[0074] This negative electrode has all the advantages of the aforementioned negative electrode materials.
[0075] In some examples, the negative electrode sheet includes: a negative current collector and a negative electrode coating layer disposed on at least one side surface of the negative current collector, the negative electrode coating layer including a conductive agent, a binder and the aforementioned negative electrode material.
[0076] The negative electrode material has a mass fraction of 70% to 85%, the conductive agent has a mass fraction of 10% to 20%, and the binder has a mass fraction of 5% to 10%.
[0077] For example, the mass fraction of the negative electrode material can be 70%, 72%, 75%, 78%, 80%, 82%, 85%, etc. The mass fraction of the conductive agent can be 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, etc. The mass fraction of the binder can be 5%, 6%, 7%, 8%, 9%, 10%, etc.
[0078] In this embodiment, the high proportion of negative electrode material fully leverages the high theoretical specific capacity of silicon-based active materials, meeting the high energy density requirements of batteries. By controlling the mass fraction of the conductive agent within the aforementioned range, electron transport efficiency can be improved, optimizing battery rate performance. Simultaneously, controlling the conductive agent proportion to avoid over-reducing the proportion of silicon-based active material and causing capacity loss. By controlling the binder mass fraction within the aforementioned range, the binder can firmly bond the negative electrode material and conductive agent together, adhering firmly to the negative electrode current collector. Furthermore, the binder's own toughness can buffer the significant volume expansion of the silicon-based active material during charging and discharging, inhibiting cracking, pulverization, and detachment. Simultaneously, controlling the binder proportion to avoid increasing electrode impedance and hindering lithium-ion migration.
[0079] In some examples, the conductive agent is selected from at least one of acetylene black and carbon nanotubes. When the conductive agent is selected from acetylene black and carbon nanotubes, the mass ratio of the two is 1:1.
[0080] The adhesive is selected from at least one of sodium alginate and styrene-butadiene rubber.
[0081] The aforementioned conductive agent possesses excellent conductivity, enabling the formation of a continuous conductive network that provides a stable electron transport path and improves electron transport efficiency. The aforementioned binder firmly bonds the negative electrode material and conductive agent together, adhering securely to the negative electrode current collector. Simultaneously, its own toughness buffers the significant volume expansion of the silicon-based active material during charging and discharging, inhibiting cracking, pulverization, and detachment of the silicon-based active material.
[0082] In the preparation of the negative electrode sheet, the negative electrode material, conductive agent, binder, and solvent are added to a double planetary mixer and mixed evenly to obtain a negative electrode slurry. The negative electrode slurry is then uniformly coated onto the surface of the negative electrode current collector, and after processes such as drying, rolling, slitting, cutting, and baking, the negative electrode sheet is obtained.
[0083] On the other hand, embodiments of this application provide a battery, which includes a casing, an electrolyte contained inside the casing, a negative electrode, a positive electrode, and a separator, wherein the negative electrode is the aforementioned negative electrode, and the positive electrode is separated from the negative electrode by the separator. Of course, the battery can also have other structures, and no specific limitation is made thereto.
[0084] In summary, the negative electrode material provided in this application has the following beneficial effects: (1) This application utilizes surface chemical modification to achieve uniform composite of heterogeneous materials. Due to the natural oxide layer (SiO) on the surface of silicon nanosheets, x The presence of MXene nanosheets (MSN) typically results in weak negative charge in aqueous solutions, leading to electrostatic repulsion between MSN and MSN nanosheets, making it difficult to directly form a uniform and stable composite structure. This application addresses this issue by modifying MSN nanosheets with a cationic surfactant. The hydrophobic end of the cationic surfactant is adsorbed onto the MSN surface via van der Waals forces, while the hydrophilic cationic head groups extend outwards, converting the MSN surface charge from negative to positive. When a dispersion of positively charged modified MSN nanosheets is mixed with a dispersion of negatively charged MSN nanosheets, a strong electrostatic attraction is generated between them. This drives the MSN nanosheets to spontaneously and uniformly anchor onto the MSN nanosheet surface or embed into the interlayer gaps, forming a closely contacted heterostructure. This self-assembly process requires no external energy, operates under mild reaction conditions, and produces a uniform composite.
[0085] (2) MXene nanosheets possess metal-like high conductivity, several to tens of times that of traditional carbon materials. In composite materials, these two-dimensional nanosheets overlap to form a three-dimensional conductive network that runs through the entire electrode. Silicon nanosheets, as the active material, are precisely anchored on this network. This structural design fundamentally solves the defect of poor intrinsic conductivity of silicon: on the one hand, the MXene network provides a fast transport channel for electrons from the current collector to the silicon nanosheets; on the other hand, the large specific surface area and surface hydrophilicity of the two-dimensional nanosheets facilitate the full wetting of the electrolyte, shortening the solid-state diffusion distance of lithium ions. The combined effect of these two factors enables silicon nanosheets to respond quickly to electrochemical reactions, significantly improving the rate performance of the material.
[0086] (3) Flexible MXene nanosheets are bonded to silicon nanosheets to form a protective layer with both high mechanical strength and good flexibility. When the silicon nanosheets expand in volume during lithiation, the MXene nanosheets buffer the expansion in two ways: first, the weak interaction between the MXene layers allows the nanosheets to slip and deform relative to each other, consuming the expansion stress within the two-dimensional plane; second, the strong interfacial bonding force between the MXene nanosheets and the silicon nanosheets provides physical constraints, limiting the expansion to a local area. This dual buffering mechanism effectively prevents the overall collapse of the electrode structure and maintains the electrical contact integrity between the active material and the conductive network.
[0087] (4) The negative electrode material is obtained by freeze drying. Water sublimates directly, silicon nanosheets are not easily oxidized, and there is no capillary contraction force. The loose three-dimensional porous network of modified silicon nanosheets and MXene nanosheets can be completely preserved. MXene nanosheets are not easy to stack, and modified silicon nanosheets are evenly dispersed, which is beneficial to improving the electrochemical performance of the negative electrode material.
[0088] The technical solution of this application will be described in detail below through specific embodiments.
[0089] In the following specific embodiments, unless otherwise specified, all operations shall be performed under normal conditions or conditions recommended by the manufacturer.
[0090] Example 1 Example 1 provides a negative electrode material, which is prepared by the following method: Step 1: Disperse 0.3g of photovoltaic silicon waste and 3mL of 20wt% polydiallyldimethylammonium chloride (PDDA, Mw=100000~200000) aqueous solution in 150mL of deionized water by ultrasonication for 1h. Stir the mixture magnetically for 1h, separate it by high-speed centrifuge, wash with deionized water to remove excess PDDA, and redisperse the modified photovoltaic silicon waste in an appropriate amount of deionized water to obtain a dispersion of modified photovoltaic silicon waste.
[0091] Step 2: Slowly add 30 mL of MXene aqueous solution (1.0 mg / mL) to the dispersion of modified photovoltaic silicon waste, stir at room temperature for 1 h, filter, and freeze-dry at -65℃ for 12 h to obtain Si@MXene composite material, i.e., anode material.
[0092] The mass ratio of MXene to photovoltaic silicon waste is 1:10, and the MXene is Ti3C2T. x T x It represents functional groups such as —O, —OH, and —F.
[0093] See Figure 2 , Figure 2 These are TEM (Transmission Electron Microscope) images and EDS (Energy Dispersive Spectrometer) images of a negative electrode material provided in Embodiment 1 of this application. Figure 2 The TEM image shows that the two-dimensional modified silicon nanosheets and MXene nanosheets achieved uniform composite formation, with the two-dimensional modified silicon nanosheets adhering to a large area of the MXene nanosheet surface. Figure 2 As can be seen from the EDS image, Ti elements are uniformly distributed on the surface of Si elements.
[0094] The negative electrode material prepared in Example 1, when used as a negative electrode material in a lithium-ion battery, exhibits a reversible specific capacity of 1128 mAh / g under a discharge rate of 3 A / g. -1 It exhibits excellent rate performance.
[0095] Example 2 Example 2 provides a negative electrode material, which is prepared by the following method: Step 1: This step is the same as in Example 1.
[0096] Step 2: Slowly add 30 mL of MXene aqueous solution with a concentration of 2 mg / mL to the dispersion of modified photovoltaic silicon waste, stir at room temperature for 1 h, filter, and freeze dry at -65℃ for 12 h to obtain Si@MXene composite material.
[0097] The mass ratio of MXene to photovoltaic silicon waste is 1:5, and the type of MXene is the same as in Example 1.
[0098] Example 3 Example 3 provides a negative electrode material, which is prepared by the following method: Step 1: This step is the same as in Example 1.
[0099] Step 2: Slowly add 30 mL of 0.5 mg / mL MXene aqueous solution to the dispersion of modified photovoltaic silicon waste, stir at room temperature for 1 h, filter, and freeze dry at -65℃ for 12 h to obtain Si@MXene composite material.
[0100] The mass ratio of MXene to photovoltaic silicon waste is 1:20, and the type of MXene is the same as in Example 1.
[0101] Comparative Example 1 Comparative Example 1 provides a negative electrode material, which is prepared by the following method: Step 1: The difference from Step 1 in Example 1 is that 0.3g of photovoltaic silicon waste is replaced with 0.3g of silicon nanoparticles with a particle size of 200nm. All other steps are the same.
[0102] Step 2: Same as step 2 in Example 1.
[0103] Comparative Example 2 Comparative Example 2 provides a negative electrode material, which is prepared by the following method: Step 1: Same as Step 1 in Example 1.
[0104] Step 2: The difference from Step 2 in Example 1 is that after filtration, the filter cake is placed in a vacuum drying oven and dried at 80°C and 0.2 kPa for 20 hours to obtain the negative electrode material.
[0105] Comparative Example 3 Comparative Example 3 provides a negative electrode material prepared by the following method: 30 mL of a 1.0 mg / mL aqueous solution of MXene was mixed with a 15 wt% aqueous solution of tetramethylammonium acetate (TMAA) and stirred to induce esterification between the carboxyl groups of TMAA and the hydroxyl groups on the surface of MXene, resulting in a positively charged TMAA-modified MXene dispersion. Unreacted TMAA was removed by washing with deionized water, and the MXene was redispersed in deionized water.
[0106] 0.3g of photovoltaic silicon waste was dispersed in a TMAA-modified MXene dispersion and stirred at room temperature for 1 hour. Self-assembly was achieved by utilizing the electrostatic attraction between the positively charged MXene and the negatively charged silicon waste. The anode material was obtained after filtration and freeze-drying.
[0107] In this example, the mass ratio of MXene to photovoltaic silicon waste was 1:10, and the freeze-drying conditions were the same as in Example 1. That is, except for the modified object and the modifier, all other parameters were the same as in Example 1.
[0108] The negative electrode material, conductive carbon black, and sodium alginate are mixed in a mass ratio of 7:2:1. Deionized water is added and stirred evenly to form a slurry. The slurry is then evenly coated onto the surface of copper foil, dried, and cut to obtain the negative electrode sheet.
[0109] Assemble a CR2032 type button cell by using a negative electrode sheet as the negative electrode and a lithium metal sheet as the counter electrode.
[0110] After battery assembly, it was allowed to stand for 12 hours. Then, constant current charge-discharge rate performance testing was conducted using an electrochemical workstation. The test voltage range was 0.01V to 1.5V. Constant current charge-discharge cycle tests were performed sequentially at current densities of 0.2A / g, 0.5A / g, 0.8A / g, 1A / g, and 3A / g. Finally, the cycle was switched to 0.2A / g for recovery. The discharge specific capacity of each cycle was recorded, and a schematic diagram of the rate performance was plotted. (See attached diagram.) Figure 3 .
[0111] from Figure 3 As can be seen, compared with Comparative Example 1, the anode materials prepared in Examples 1-3 all exhibited higher discharge specific capacity at current densities of 0.2 A / g, 0.5 A / g, 0.8 A / g, 1 A / g, and 3 A / g, and showed higher capacity recovery rates when recovering to 0.2 A / g, indicating excellent rate performance. Among them, the anode material prepared in Example 1 showed the best rate performance.
[0112] In addition, this application also conducted constant current charge-discharge tests on the batteries corresponding to Example 1 and Comparative Example 2 at a current density of 0.1 A / g. At a current density of 0.1 A / g, the discharge specific capacity corresponding to Example 1 was 2823 mAh g. -1 The discharge specific capacity of Comparative Example 2 is only 2388 mAh g. -1 The discharge specific capacity was reduced by 17.2% compared to Example 1. The reason for the difference in discharge specific capacity is that Example 1 used freeze drying, where the filter cake was rapidly pre-frozen with liquid nitrogen, causing water to directly sublimate into water vapor. The drying process was at a low temperature, making it difficult for the silicon nanosheets to oxidize. In contrast, Comparative Example 2 was vacuum dried at 80°C. Although the vacuum level was low (0.2 kPa), the trace dissolved oxygen and moisture remaining in the filter cake reacted with the surface of the silicon nanosheets under high temperature conditions, causing the silicon to be oxidized to silicon oxide, resulting in a significant decrease in discharge specific capacity. In addition, the capillary surface tension generated by the evaporation of liquid water during the high-temperature vacuum drying process also caused the MXene nanosheets to stack and agglomerate, and the three-dimensional network structure to partially collapse, further affecting the electrochemical performance of the material.
[0113] This application also included electrochemical impedance spectroscopy (EIS) testing of the battery. The testing method is as follows: By applying a small-amplitude AC sinusoidal potential wave of different frequencies to the battery, the change in impedance is analyzed based on the change in wave frequency, which directly reflects the internal resistance information of the battery. Using a CHI760E electrochemical workstation, the interfacial resistance of the assembled button half-cell was tested under conditions of 100 kHz to 0.01 Hz and an amplitude of 5 mV. The test results are shown in [reference needed]. Figure 4 .
[0114] from Figure 4 As can be seen, the semicircle diameters corresponding to the Nyquist curves of Examples 1 to 3 are all smaller than those of Comparative Example 1. In particular, Example 1 exhibits the smallest semicircle diameter in the high-frequency region of its Nyquist curve, indicating the lowest charge transfer resistance (Rct). This is attributed to the tight surface-to-surface contact and the penetrating three-dimensional conductive network between the modified silicon nanosheets and MXene nanosheets. The two-dimensional structure of the silicon nanosheets effectively shortens the lithium-ion transport path, while the highly conductive MXene material effectively enhances the overall electronic conductivity of the composite material, synergistically accelerating charge transfer dynamics.
[0115] In contrast, the Nyquist curve of Comparative Example 1 shows the largest semicircle diameter in the high-frequency region, indicating the highest charge transfer resistance. This is because the modified silicon nanoparticles are spherical, and their contact with the MXene nanosheets is point-to-surface. Compared to the surface-to-surface contact in Examples 1-3, the effective contact area of point-to-surface contact is significantly reduced, resulting in fewer electron transport channels at the interface and a significant increase in interface impedance. Furthermore, silicon nanoparticles are prone to aggregation. When a large number of particles stack and aggregate, they disrupt the MXene conductive network, ultimately leading to even higher charge transfer resistance and worsened electrochemical reaction kinetics.
[0116] In addition, this application also conducted EIS tests on pristine MXene, TMAA-modified MXene, the negative electrode material provided in Example 1, and the negative electrode material provided in Comparative Example 3. The EIS test results showed that the Rct of pristine MXene was 32.28 Ω, while the Rct of TMAA-modified MXene significantly increased to 83.66 Ω. The Rct of the negative electrode material provided in Comparative Example 3 was 132.97 Ω, and the Rct of the negative electrode material provided in Example 1 was 72.33 Ω. The reason for the progressively increasing Rct is that TMAA esterification modification leads to a decrease in the conductivity of MXene itself. TMAA forms covalent bonds with the hydroxyl groups (-OH) on the MXene surface through the esterification reaction, consuming the active functional groups on the MXene surface. After the esterification reaction, the hydroxyl groups on the MXene surface are replaced by organic ester groups (-O-CO-CH3), forming an insulating coating layer on the surface of the MXene conductive framework, blocking the electron transport path on the MXene surface, resulting in a significant increase in Rct. Furthermore, (CH3)4N + Intercalation into the MXene interlayer increases the interlayer spacing, hinders the tunneling transport of interlayer electrons, further reduces the conductivity of MXene, increases the interface distance and interface resistance, and causes the Rct of the negative electrode material provided in Comparative Example 3 to increase further.
[0117] The above description is only for the purpose of enabling those skilled in the art to understand the technical solution of this application, and is not intended to limit this application. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.
Claims
1. A negative electrode material, characterized in that, The negative electrode material includes modified silicon nanosheets and MXene nanosheets, wherein the modified silicon nanosheets are attached to the surface of the MXene nanosheets.
2. The negative electrode material according to claim 1, characterized in that, The modified silicon nanosheets have a planar lateral dimension of 0.1 μm to 10 μm.
3. The negative electrode material according to claim 1, characterized in that, The thickness of the modified silicon nanosheets is 100nm~200nm.
4. The negative electrode material according to claim 1, characterized in that, The modified silicon nanosheets are obtained by modifying silicon nanosheets with cationic surfactants.
5. The negative electrode material according to claim 4, characterized in that, The cationic surfactant is selected from at least one of polydiallyldimethylammonium chloride, polymethacryloyloxyethyltrimethylammonium chloride, and polyethyleneimine.
6. The negative electrode material according to claim 4, characterized in that, The silicon nanosheets are selected from photovoltaic silicon waste.
7. The negative electrode material according to claim 1, characterized in that, The MXene nanosheets are selected from Ti3C2T x Ti2CT x V2CT x At least one of Nb2CTx; T x The functional groups of the MXene nanosheets are represented.
8. A method for preparing a negative electrode material, characterized in that, The negative electrode material is as described in any one of claims 1 to 7, and the preparation method includes: A dispersion of modified silicon nanosheets was obtained by modifying silicon nanosheets with a cationic surfactant. Preparation of dispersions of MXene nanosheets; The dispersion of the modified silicon nanosheets was mixed with the dispersion of the MXene nanosheets, and then freeze-dried to obtain the negative electrode material.
9. A negative electrode sheet, characterized in that, The negative electrode sheet comprises the negative electrode material according to any one of claims 1 to 7 or the negative electrode material prepared by the preparation method according to claim 8.
10. A battery, characterized in that, The battery includes: a housing, an electrolyte contained inside the housing, a negative electrode, a positive electrode, and a separator, wherein the negative electrode is as described in claim 9, and the negative electrode and the positive electrode are separated by the separator.
